Growth and survival to weaning of crosses of Ayrshire, Brown swiss and Sahiwal cattle. - Kahi, A.K. (Egerton University, 1995)
A total of 1443 records from a private ranch in the coastal lowland tropics of Kenya were used to estimate the comparative calf performance to weaning of the different crosses of Ayrshire (A), Brown Swiss (B) and Sahiwal (S). Individual and maternal additive and heterotic effects for, and heritabilities of, and correlations among, the preweaning traits were also estimated. A fixed effects least squares model was used for analysis of growth traits while a logistic model was employed in the analysis of survival rate (SRATE). Linear coefficients for breed and heterosis effects were substituted for genetic group effects to estimate individual and maternal additive genetic and heterotic effects. Heritabilities were estimated by derivative-free restricted maximum likelihood procedure in a univariate analyses fitting an animal model. Genetic and phenotypic correlations were estimated by paternal half-sib procedures. Mean birth weight (BWT) was 30.9 ? 0.18 kg, 93% of calves survived to weaning, and mean preweaning average daily gain (PADG) was 488 + 2.10 g/day. Calves took an average of 126 days to reach the mean weaning weight of 92 kg. The effect of breed of sire was not statistically significant (P > 0.05) for any of the preweaning traits. The effect of dam genotype was only statistically significant (P < 0.001) for BWT with calves from three-breed cross dams having heavier BWT than those from two-breed rotational dams. Calf genotype had a significant effect (P<O.OOl) on BWT. BWT tended to increase as the percentage of Bos taurus genes increased. Mating system significantly (P<O.OI) affected BWT and PADG with the two-breed rotational crosses having lower BWT and higher P ADG than the three-breed rotational crosses, although the scale of the post-natal differences were small. The individual and maternal additive genetic effects for A and S were not significant (P > 0.05) for any of the traits. Similarly, the individual heterotic effect of B. taurus - B. indicus heterozygosity was not significant (P>0.05) for calf performance. A small effect of AS individual heterosis on P ADG was found. It was estimated that FI AS calves gained 26 g/day faster (p < 0.1) than . the mean of the purebred A and S calves. The maternal heterotic effect of B. taurus - B. indicus heterozygosity for BWT was -3.19 + 1.25 kg and of opposite sign to estimates reported in the literature. Heritability estimates were 0.14 ? 0.08 for BWT, 0.21 + 0.08 for PADG, 0.24 ? 0.09 for WAGE and 0.01 ? 0.07 for SRATE. The genetic and phenotypic correlations between PADG and WAGE were high and negative (-0.87 + 0.49 and -0.74, respectively), indicating that a high PADG vi resulted in a desirable younger WAGE. In this production environment, selection on PADG is likely to yield genetic progress. Both additive genetic breed differences and heterosis effects were small in the B. taurus - B. indicus heterozygosity, possibly due to the favourable feeding and management conditions. The absence of any major variation among calf genotypes showed that the individual and maternal breed and heterotic effects of the sire breeds and dam genotypes summed to give very similar aggregate preweaning performance for all traits except BWT. Therefore, in this herd, no emphasis should be given to preweaning performance when selecting among these sire breeds and mating systems. These decisions will be determined by relative lactation and reproduction performances. It is concluded that while crossbreeding results in improvement in the performance of the current generation, continued improvement of performance will require an efficient within-breed selection programme for the economically important production traits.